2019
DOI: 10.3390/rs11242958
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Geostationary Satellites for Aerosol Remote Sensing Based on Critical Surface Albedo

Abstract: Geostationary satellites are increasingly used for the detection and tracking of atmospheric aerosols and, in particular, of the aerosol optical depth (AOD). The main advantage of these spaceborne platforms in comparison with polar orbiting satellites is their capability to observe the same region of the Earth several times per day with varying geometry. This provides a wealth of information that makes aerosol remote sensing possible when combined with the multi-spectral capabilities of the on-board imagers. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Several times per hour, each satellite acquires an image of the Earth’s disk observed from its position along the geostationary orbit, at several visible and infrared wavelengths, and at a spatial resolution between 1 and 3 km. The high number of images per day provided by geostationary satellites allows for a robust detection of aerosols 40 . Global maps of daily-averaged total AOD at 640 nm at 0.1° of resolution were retrieved from the GEO-ring following Ceamanos et al 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Several times per hour, each satellite acquires an image of the Earth’s disk observed from its position along the geostationary orbit, at several visible and infrared wavelengths, and at a spatial resolution between 1 and 3 km. The high number of images per day provided by geostationary satellites allows for a robust detection of aerosols 40 . Global maps of daily-averaged total AOD at 640 nm at 0.1° of resolution were retrieved from the GEO-ring following Ceamanos et al 41 .…”
Section: Methodsmentioning
confidence: 99%
“…2b) close to 0 in these regions, which means that the AOD sensitivity from SEVIRI observations is low in this case. This low information content is due to a combination of factors including lower aerosol scattering and brighter surface reflectance, usually happening at higher scattering angles (Ceamanos et al, 2019). Figure 4 shows that refining the surface reflectance initially estimated by iAERUS-GEO improves AOD retrievals, especially when the sensitivity to aerosols is low.…”
Section: Aod and Surface Reflectance Retrievalmentioning
confidence: 99%
“…This research suggested that, at the CSA, additional aerosol loading should not generate a net change in the upward radiance since the enhanced aerosol backscattering at the TOA is balanced by the increased attenuation of light by the aerosol layer [44]. Great efforts have been made by exploiting this critical value concept to identify the relationships between CSA and SSA [45][46][47][48] and further studying the implications of the CSA in aerosol remote sensing [38,42,49,50].…”
Section: Introductionmentioning
confidence: 99%